(untitled) (Research, Society and Development, 2022)
The present work aims to identify memories about the presence and characterization of black characters in the trajectory of literary reading of high school teachers of a school in the region of Cariri-Ceará. For this purpose, we used the research format of exploratory, quali-quantitative approach, performing bibliographic studies in books, scientific articles and dissertations, in addition to the application of a data collection questionnaire for educators of the aforementioned educational institution. Thus, the analysis of the collected information was based on the readings made during the bibliographic study on the theme and considering the human being as a subject that is constructed from the historical-social relations. As results, we obtained elements that indicate the black character’s payment of memory, the ratification of the myth of racial democracy and the whitening of the Brazilian population, the identification of the black with the marginalization, misery, submission; but components were also obtained that indicate a (re)reading of history and point to the process of combating racism and to the affirmative of black culture and identity.components were also obtained that indicate a (re)reading of history and point to the process of combating racism and to the affirmative of black culture and identity. Thus, the literature is shown as a powerful interventional instrument for the construction of new knowledge and experiences.